2012
DOI: 10.1364/ol.37.001640
|View full text |Cite
|
Sign up to set email alerts
|

66 W average power from a microjoule-class sub-100 fs fiber oscillator

Abstract: Performance scaling of passively mode-locked ultrashort-pulse fiber oscillators in terms of average power, peak power, and pulse energy is demonstrated. A very-large-mode-area fiber laser in an all-positive group-velocity-dispersion ring cavity configuration with intracavity spectral filter, mode-locked by nonlinear polarization evolution, emits 66 W of average power at 76 MHz repetition rate, corresponding to 0.9 μJ pulse energy. The pulses are dechirped to 91 fs outside the cavity with an average power of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…Lefrancois et al reported a dissipative-soliton laser with Yb-doped photonic-crystal fiber (PCF) with a 40-µm core diameter replacing the ordinary gain fiber [47]. The laser generated 100-nJ and 100-fs pulses, for a peak power of 1 MW, while the average power was 8 W. By use of a photonic crystal (PC) rod with even larger mode area, Baumgartl et al achieved 850-nJ pulses, 6 MW peak power, and over 60 W average power from a dissipative-soliton laser [48]. These remarkable performance levels currently require sacrificing some of the benefits of standard fiber, but they highlight the potential of mode-locked fiber lasers.…”
Section: Advances In High-energy Femtosecond Fiber Oscillatorsmentioning
confidence: 99%
“…Lefrancois et al reported a dissipative-soliton laser with Yb-doped photonic-crystal fiber (PCF) with a 40-µm core diameter replacing the ordinary gain fiber [47]. The laser generated 100-nJ and 100-fs pulses, for a peak power of 1 MW, while the average power was 8 W. By use of a photonic crystal (PC) rod with even larger mode area, Baumgartl et al achieved 850-nJ pulses, 6 MW peak power, and over 60 W average power from a dissipative-soliton laser [48]. These remarkable performance levels currently require sacrificing some of the benefits of standard fiber, but they highlight the potential of mode-locked fiber lasers.…”
Section: Advances In High-energy Femtosecond Fiber Oscillatorsmentioning
confidence: 99%
“…16,44 Lasers working with large normal GDD, even with all normal dispersion elements, 43 can support wave-breaking free pulses of very large energy. For example, Baumgartl et al 45 have even demonstrated 66 W of average power and µJ pulses directly from an oscillator without subsequent amplification. However, for the quietest operation, with both the lowest phase and amplitude noise most suitable for comb applications, it is desirable to operate the laser near net zero cavity GDD.…”
Section: Yb:fiber Oscillatorsmentioning
confidence: 99%
“…The corresponding peak power is strong enough for nonlinear microscopy (157, 158). Another approach is to utilize large-mode-area fibers as gain media, which leads to an output energy of up to 0.9 μJ (159), but this approach sacrifices some of the compatibility and flexibility of fiber lasers.…”
Section: Fiber Laser Sources For Crs Microscopymentioning
confidence: 99%